Some aspects of the labour history of Bengal in the nineteenth century two views - Chakrabarty, Dipesh 1948-; Das Gupta, Ranajit 1932-1998 (Oxford University Press, 2019)
Part of the 'Occasional Papers' series of CSSSC, this essay is a brief, and sharply posed, exchange between Dipesh Chakrabarty and Ranajit Das Gupta on working class consciousness in Bengal. it posits that this consciousness is not a mechanical outcome of the capitalist mode of production, it is not a thing but a process; that even failure must be taken on board in order to flesh out that process; that not only was the working class present (and therefore conscious) of its own making, but drew from rich pre-capitalist cultural traditions of dissent, rebellion and republicanism. 0the essay asks pertinent questions about the morality of labour, history of peasant revolts, capitalist intervention, religious discrimination among labourers etc
Keywords: Geschichte 1875-1899; Klassenbewusstsein; Arbeiterklasse; Bengalen; Labor / India / Bengal / History; Labor; India / Bengal; History